Kepemimpinan Manajerial Kepala Madrasah terhadap Profesionalisme Guru: Kajian Empiris di MTs Taufiqiyatul Asna Kediri - Adib Afandi adib; fadly Fadly Usman; Ashari Ashari (CV Alifba Media, 2025)
The right strategy will influence the success in developing teacher competencies. Effective management implementation encompasses various important aspects, such as strategic planning, organizing, professional development through training, and systematic performance evaluation. The objectives of this research are: 1) To analyze the implementation of madrasah principal management in enhancing teacher professionalism at MTs Taufiqiyatul Asna, 2) To identify the supporting and inhibiting factors in the management implementation process.The type of research employed in this study is qualitative with a case study approach at MTs Taufiqiyatul Asna.The results of this study are as follows: First, the implementation of madrasah principal management has been successfully applied through strategies such as strategic planning, organizing, professional development, and systematic performance evaluation. These strategies have positively contributed to the enhancement of teacher competencies in pedagogical, professional, social, and personal aspects. Second, the factors supporting the success of this implementation include staff commitment, community support, and adequate facilities. However, there are also inhibiting factors such as budget constraints and resistance to change. The madrasah principal has taken steps to overcome these challenges, including seeking additional funding sources and providing training to improve technology adaptation among teachers.